Faunistic Studies on the Genus Culiseta (Diptera:Culicidae) in Guilan Province - Sh Azari-Hamidian; M.A Joeafshani; A.R Rassaei; M Mosslem (Journal of Kerman University of Medical Sciences, 2003)
To study mosquito ( Diptera : Culicidae) fauna in Guilan province (Caspian sea littoral , North of Iran ), an investigation was carried out during April to December 2000. The whole set of 2478 adult specimens from 64 habitats and 6656 larvae from 127 larval breeding places was collected . Three species of the genus Culiseta were identified as follow: 1- Cs. longiareolata 2- Cs. morsitans 3- Cs. Annulata. In this study Cs. morsitans and its subgenus (Culicella) were reported for the first time in Iran.In this article the distribution and percentage of the frequency of the genus Culiseta in Guilan province were discussed.